2015
DOI: 10.3390/rs70404678
|View full text |Cite
|
Sign up to set email alerts
|

Building Deformation Assessment by Means of Persistent Scatterer Interferometry Analysis on a Landslide-Affected Area: The Volterra (Italy) Case Study

Abstract: Abstract:In recent years, space-borne InSAR (interferometric synthetic aperture radar) techniques have shown their capabilities to provide precise measurements of Earth surface displacements for monitoring natural processes. Landslides threaten human lives and structures, especially in urbanized areas, where the density of elements at risk sensitive to ground movements is high. The methodology described in this paper aims at detecting terrain motions and building deformations at the local scale, by means of sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
76
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(76 citation statements)
references
References 38 publications
0
76
0
Order By: Relevance
“…The higher spatial resolution and less revisiting time of this satellite would be suitable to measure the differential deformation of different sectors of single buildings. Angular distortions caused by differential settlement processes, where only vertical displacement is assumed, could be investigated [24,26]. Furthermore, it can be used as a tool to monitor possible displacements after remedial stabilization solutions have been carried out.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The higher spatial resolution and less revisiting time of this satellite would be suitable to measure the differential deformation of different sectors of single buildings. Angular distortions caused by differential settlement processes, where only vertical displacement is assumed, could be investigated [24,26]. Furthermore, it can be used as a tool to monitor possible displacements after remedial stabilization solutions have been carried out.…”
Section: Discussionmentioning
confidence: 99%
“…Even though high spatial resolution sensors, i.e., TerraSAR-X or CosmoSkyMed, are the most adequate for studying urban areas [22][23][24], the Synthetic Aperture Radar (SAR) images are acquired under request, and thus no images might be available to study past events. On the other hand, several works have demonstrated the usefulness of C-band SAR images acquired by medium spatial resolution sensors such as ERS and ENVISAT satellites to monitor urban structures [22,[25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…The outcropping terrains are mainly Miocene-Pliocene clayey and sandy marine formations (respectively "Blue Clays" and "Villamagna sands") that represent the sedimentary filling of the basin. Calcarenites and limestones close the marine sedimentary succession and constitute the tableland on which Volterra city was built [37]. Fine and coarse detritic sediments (e.g., conglomerates and breccias), developed in lacustrine or lagoonal cycles or in a continental fluvial-deltaic environment are also present.…”
Section: Environmental Settingmentioning
confidence: 99%
“…Notti et al [22] found a relationship between the severity of damage, the duration of ground deformation and the age of buildings. Bianchini et al [21] concluded that building damage was mainly controlled by the combination of terrain morphology and the type of foundation that had been employed.…”
Section: Comparasion Of Damages Map and Deformationmentioning
confidence: 99%
“…For instance, the use of high-resolution X-band data allows increasing the density of measurements over individual building, and might be of interest for other applications (e.g., estimation of differential settlements for each building, see [21,53]). Additionally, the information provided by our map can be completed by specifying the type of building evaluated (education centres, health facilities) following the requirements for damage and loss data sharing standard for the Sendai Framework for Disaster Risk Reduction [54].…”
Section: Vulnerable Buildings Map Potential and Limitsmentioning
confidence: 99%